UNIVERSITY PORTAL USER EXPERIENCE: A CASE STUDY OF UNIDEL - Oveh O., Richard; Atomatofa, E; Okafor O., U (FUDMA JOURNAL OF SCIENCES, 2025)
University portal websites play a crucial role in providing academic information and services to students, faculty, and staff. Research has shown that usability and user experience are key factors in the success of these portals. This paper evaluates the usability and user experience of UNIDEL’s portal to improving digital experience in universities. Quantitative method was used to obtain data from undergraduate students at UNIDEL. A google form was created and dropped randomly in various WhatsApp groups. 70 responses was obtained. The result shows that while the portal effectively supports administrative tasks, its potential as an engagement tool remains underutilized. Enhancing interactivity by linking to learning management systems or adding richer, more responsive support materials could transform the portal from a predominantly transactional service into a more dynamic hub that encourages daily use and deeper academic involvement.